Assessment of oral health status of pregnant women participating in a family health program in the city of Lucas do Rio Verde - MT - Brazil - Aline Sampieri Tonello; Maria Angélica Botega Ortuzal Zuchieri; Vanessa Pardi (Universidade Estadual de Campinas, 2016)
The aim of this study was to assess the oral health status of pregnant women. Eighty-eight (88) women who frequented the Pre-Natal program of the six Family Health Programs in the municipality of Lucas do Rio Verde-MT, Brazil, were assessed by clinical exam using the DMFT and CPI indexes. A DMFT index of 11.08 was found, and with regard to CPI, 40% of the pregnant women presented a sextant with bleeding. It was concluded that it is necessary to reinforce knowledge about oral health of the pregnant women examined, by means of preventive/educational programs with the purpose of improving the DMFT and CPI indexes.